Case report: a novel frameshift mutation in the mitochondrial cytochrome c oxidase II gene causing mitochondrial disorder - Laura Kytövuori; Mikko Kärppä; Hannu Tuominen; Johanna Uusimaa; Markku Saari; Reetta Hinttala; Kari Majamaa (BIOMED CENTRAL LTD, 2022)
Background: Mitochondrial cytochrome c oxidase 2, MT-CO2, encodes one of the three subunits, which form the catalytic core of cytochrome c oxidase (COX), complex IV. Mutations in MT-CO2 are rare and the associated phenotypes are variable including nonsyndromic and syndromic forms of mitochondrial diseases.Case presentation: We describe a 30-year-old man with cognitive decline, epilepsy, psychosis, exercise intolerance, sensorineural hearing impairment, retinitis pigmentosa, cataract and lactic acidosis. COX-deficient fibers and ragged red fibers were abundant in the muscle. Sequencing of mitochondrial DNA (mtDNA) revealed a novel frameshift mutation m.8156delG that was predicted to cause altered C-terminal amino acid sequence and to lead to truncation of the COX subunit 2. The deletion was heteroplasmic being present in 26% of the mtDNA in blood, 33% in buccal mucosa and 95% in muscle. Deletion heteroplasmy correlated with COX-deficiency in muscle histochemistry. The mother and the siblings of the proband did not harbor the deletion.Conclusions: The clinical features and muscle histology of the proband suggested a mitochondrial disorder. The m.8156delG deletion is a new addition to the short list of pathogenic mutations in the mtDNA-encoded subunits of COX. This case illustrates the importance of mtDNA sequence analysis in patients with an evident mitochondrial disorder.